Potential and Performance of Accelerated Solvent Extraction (ASE) in Obtaining Bioactive Compounds from Bee Propolis as Compared with Other Extraction Methods - Elmer-Rico E. Mojica; Jozlyn M Charland; Custer C Deocaris; Jose Rene L Micor (Journal of Tropical Life Science, 2021)
Propolis is a natural resinous substance collected by honeybees from buds and exudates of trees. The material has attracted much attention in recent years as a functional food component since it possesses various biological properties, including antimicrobial, antioxidative, and anti-ulcer properties. In this study, the performance of accelerated solvent extraction (ASE) was assessed and compared with varying methods of extraction: soaking (maceration), ultrasonication, and microwave-assisted methods. Gas chromatography-mass spectrometry (GC-MS) and other spectroscopic techniques, such as absorbance and fluorescence, were employed to assess the efficiency in the extraction of natural products. The antioxidant activity and phenolic content of the different extracts were also determined. Results showed samples obtained from the microwave method showed the highest yield. Some issues and recommendations on the application of ASE for extracting natural products from bee propolis were discussed.